Real-time face detection and recognition - Tang, Ying Hao (2014)
Real-time face detection (RTFD) and recognition is used widely in many areas from tagging faces on Facebook, custom services at airports and to unlocking phones through a face recognition application. The main functionality involves verifying the identity of a person and in doing so, applying that result in various other applications.. In this report, we study various face detection and recognition techniques and use an appropriate one to develop a program that can perform real-time face detection and recognition.